Phaseolus beans - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1989)
The main activities on Phaseolus beans (in vitro culture techniques and biochemical and molecular markers) conducted in 1988 by CIAT`s Biotechnology Research Unit are summarized. (CIAT)